Hydrogen Bond Activation by Pyridinic Nitrogen for the High Proton Conductivity of Covalent Triazine Framework Loaded with H3PO4. Issue 23 (11th November 2022) - Liu, Manying; Deng, Wei‐Hua; Wang, Xueqing; Liu, Jing; Jin, Shangbin; Xu, Gang; Tan, Bien
Abstract: Under high temperature anhydrous conditions, it is still a formidable challenge to improve the performance of proton‐conducting materials based on H3 PO4 and elucidate its proton conduction mechanism. Herein, a highly stable covalent triazine frameworks (CTFs) based on H3 PO4 is reported. The more pyridinic nitrogen CTFs contain, the higher proton conductivity is. Compared with H3 PO4 @CTF−L with less pyridinic nitrogen, H3 PO4 @CTF−H has a higher proton conductivity of 1.6×10 −1  S cm −1 at 150 °C under anhydrous conditions, which does not decay after about 18 months exposure in air. The high proton conductivity is associated with the formation and breaking of the activated Ntriazine ⋯H + ⋯H2 PO4 − pairs by pyridinic nitrogen of CTFs. The outstanding long‐term stability is mainly attributed to the ultra‐strong triazine skeleton structure of CTFs. Abstract : Flow of protons : The proton transport of H3 PO4 @CTFs relies on the reorganization of activated hydrogen bonds of H3 PO4 by the alkaline pyridinic nitrogen under anhydrous conditions. H3 PO4 @CTFs is a very stable and high‐performance proton exchange membrane material.